Pelaksanaan Pendaftaran Tanah Lintas Sektor (Lintor) di Kantor Pertanahan Kota Kupang Sebagai Upaya Memperoleh Kepastian Hukum Hak Atas Tanah - Miftahul Chair; Agustinus Hedewata; Orpa J Nubatonis (Jurnal Hukum dan Sosial Politik, 2024)
Cross-sector land registration is land registration with subsidized assistance for low- income people who work in small and medium enterprises, SMEs, agriculture, fishermen, and fish farmers, in this case financing land rights certification services at the land office. That is how the issue is stated. (1) How Kupang City should go about implementing cross-sector land registration. (2) What are the challenges facing Kupang City in adopting cross-sector land registration? (3) How may cross-sector land registration be implemented in Kupang City? Empirical research is the methodology employed, and data is gathered through a literature review and interviewing 20 respondents. The findings of the study demonstrate (1) Kupang City's cross-sector land registration implementation procedure. Cross-sector land registration is implemented sporadically, making it a cross-sectoral process. sector comes before the gathering of legal data. (2) Obstacles to the implementation of cross-sector land registration in Kupang City include many incomplete documents, absences during the socialization of land title certificates, and problems with the applicant's land. (3) The solution to the obstacles to implementing cross-sector land registration is that the land authorities carry out monitoring and evaluation every week From the onset to the conclusion of the cross-sector implementation, and the community participates more in cross- sector implementation activities. This research has led to the following conclusions: (1) cross-sector land registration implementation Planning, negotiation, team building, gathering legal data, certification, and reporting are the phases of implementation that will take place in Kupang City based on the decision made by the head of the Kupang City Land Office. (2) Barriers to the implementation of cross-sector land registration In Kupang City, obstacles occur internally and externally, internal land parties must build relationships with related agencies and externally there are still many incomplete files, lack of community participation and land problems. (3) How to get around roadblocks in the way of Kupang's cross-sector land registration implementation; how to have officers be more proactive in reaching out to pertinent agencies and supplying information about cross-sector land registration.